Concepção, especificação, implementação e avaliação de aplicação web para prestadores de serviços. - SOUZA, Maykon Araújo de (2020)
This work makes a study about the development (involving design, specification, implementation and evaluation) of a WebApp application, whose objective is the intermediation between interested in services and service providers. The tool is called Booszinga. The majority of service providers do not have the financial capital to advertise their new business in the short term, and the Booszinga tool meets this need. The tool assists service providers in the creation of a web page, available in an administrative area, in which they can register performance categories, portfolio, professional profile, prices practiced and describe their experiences. This information is made available on the online platform. Potential clients can consult and find the service provider that best meets their needs, for business closing. The system was developed using agile methodology with an influence of interactive and incremental modeling, using UML for specification. The implementation was done in the PHP language, with the help of the Codeigniter, Bootstrap and JQuery frameworks and the database created in MySql, using the database management system (DBMS), phpmyadmin. The evaluation of the usability of the tool was done by specialists in IHC and by end users, and stated that the initial objectives were achieved satisfactorily.